The wisdom of the crowd in dynamic economies - Pietro Dindo; Filippo Massari (Theoretical Economics, 2020)
The wisdom of the crowd applied to financial markets asserts that prices represent a consensus belief that is more accurate than individual beliefs. However, a market selection argument implies that prices eventually reflect only the beliefs of the most accurate agent. In this paper, we show how to reconcile these alternative points of view. In markets in which agents naively learn from equilibrium prices, a dynamic wisdom of the crowd holds. Market participation increases agents' accuracy, and equilibrium prices are more accurate than the most accurate agent.
Keywords: D01; D53; G1; 330; Wisdom of the crowd; heterogeneous beliefs; market selection hypothesis; naive learning